Folk Art and Social Change in Ayodhya: Visual Practices among Rural Marginalized Communities (KALAA SAMIKSHA, 2025)
Rich in biodiversity and useful art resources, Ayodhya is a highly significant place for folk and local art traditions. This paper explores the role of folk art and rural craft traditions of the rural marginalized communities of Ayodhya as active agents of social change. Through visual culture and art historical exploration, it examines how traditional practices such as ritual decoration, terracotta art, traditional murals, clay and wood sculptures, embroidery and weaving and other useful folk arts are being reimagined as a means of resistance and promoting social resilience, especially by men and women from the lower and backward classes. Based on a mixed analysis of fieldwork as well as ethnographic visual analysis, ecological awareness, contextualization of rural identity and caste identity, this paper argues that folk art in contemporary Ayodhya is not merely aesthetic or devotional, but is also a living and evolving resource of political, communal and resistance.  These folk art practices challenge collective identity, cultural appropriation as well as dominant legacies and narratives in Ayodhya and offer a counter-archive to state-sponsored religious monumentalism, besides advocating for social justice, marking social change.